Synthesis of imidazo[1, 2‐a]pyridines via the silver acetate‐catalyzed Groebke‐Blackburn‐Bienayme reaction with ethylene glycol as a biodegradable and sustainable solvent. (21st January 2020) - Hussain, Mustafa; Liu, Jianhui; Fu, Lu; Hasan, Mehdi
Abstract: An efficient, silver‐based catalytic system has been designed for the synthesis of biologically important 3‐aminoimidazo‐fused heterocycles via the Groebke‐Blackburn‐Bienayme reaction, in which AgOAc was used as a catalyst and ethylene glycol as a solvent from isocyanides, various aryl aldehydes and an 2‐amino heterocycle were also used. Good to excellent yields, high atomic economy and environmentally friendly conditions are the potential features of this one‐pot process. Abstract :